ChemInform Abstract: Efficient Synthesis of (Arylethynyl)pyrrolo[2, 3‐d]pyrimidines by Stille Coupling. Issue 33 (August 2015) - Bucevicius, Jonas; Tumkevicius, Sigitas
Abstract A wide range of new pyrrolo[2, 3‐d]pyrimidine derivatives, including those with different arylethynyl groups in position C‐2 and C‐4 of the heterocycle, are obtained by palladium‐catalyzed cross‐coupling reaction of 2, 4‐dichloro‐7‐methylpyrrolo[2, 3‐d]pyrimidine (I) with (arylethynyl)tributylstannanes.